Doctoral Students' Experiences, Self-Efficacy, and Sense of Belonging Related to Academic Writing in an Online Program - Keshrie Naidoo; Laura Quaynor; Yuyang Shen (MDPI AG, 2023)
Considering the expansion of online graduate education, higher education practitioners must support student belonging and academic writing in this growing context. The purpose of this mixed-methods study was to use social cognitive theory to explore how students in an online Doctor of Education program experience becoming academic writers and to examine trends in students' belonging and writing self-efficacy. This explanatory sequential design study included quantitative data collection via an electronic survey followed by individual and focus group interviews with participants. Seventy-four students completed the survey (29% response rate) and eleven students participated in interviews. Survey results revealed that students had a moderate to high sense of belonging related to the writing process and a significant negative correlation between writing self-efficacy and belonging uncertainty. Qualitative analysis of the interviews resulted in five themes: (1) writing is experienced as a journey, (2) unclear expectations are painful, (3) English is viewed as a privilege, (4) peer support is needed, and cannot be forced, and (5) developing writers view writing as a craft and identified writing tools. This study provides supporting evidence that belonging is possible in online doctoral education. Recommendations for practice include the strategic engagement of peers and clear, timely notes from instructors.